2020
DOI: 10.3892/etm.2020.9172
|View full text |Cite
|
Sign up to set email alerts
|

Fetal thymus in the middle and late trimesters: Morphometry and development using post‑mortem 3.0T MRI

Abstract: The present study aimed to investigate the anatomical microstructure, features and signals of the fetal thymus by 3.0T FS-T2 weighted turbo spin echo sequences, which could provide imaging evidence for the evaluation of early-stage development of fetal thymus. In addition, the T2-weighted three-dimensional (3D) sequences and the 3D processing may contribute to the establishment of reference ranges for the fetal thymus. A total of 64 specimens obtained from the fetuses of 16-39 weeks of gestational age (GA) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Results from the study found only four 2D parameters correlated with MR-derived thymus volume [30]: 3VV TD, APD and perimeter, and 3VT TD. The variation in correlation between different 2D measurements and TV may be attributable to significant variability in thymus shape even within healthy fetuses [31], where some thymuses have a more globular appearance and others more diffuse. This is demonstrated in Figs.…”
Section: Comparison Of 2d-ultrasound and 3d-mr Thymus Measurementsmentioning
confidence: 99%
“…Results from the study found only four 2D parameters correlated with MR-derived thymus volume [30]: 3VV TD, APD and perimeter, and 3VT TD. The variation in correlation between different 2D measurements and TV may be attributable to significant variability in thymus shape even within healthy fetuses [31], where some thymuses have a more globular appearance and others more diffuse. This is demonstrated in Figs.…”
Section: Comparison Of 2d-ultrasound and 3d-mr Thymus Measurementsmentioning
confidence: 99%